COST-EFFECTIVENESS ANALYSIS OF ECOLOGICAL POLICY INSTRUMENTS AND ENVIRONMENTAL ACTIVITY - Vladimir N. Kurdyukov; Liparit K. Badalyan; Alla M. Aleynikova (Advanced Engineering Research, 2012)
The theoretical and analytical basis of the economic assessment technique for the ecological policy and environmental policy actions results as regards to the sustainable development promotion is offered.